2003
DOI: 10.1046/j.1365-2249.2003.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Avidity progression of dietary antibodies in healthy and coeliac children

Abstract: SUMMARYIn most individuals minute amounts of food proteins pass undegraded across the intestinal mucosa and trigger antibody formation. Children with coeliac disease have enhanced antibody production against gliadin as well as other dietary antigens, e.g. b -lactoglobulin, in cow's milk. Antibody avidity, i.e. the binding strength between antibody and antigen, often increases during antibody responses and may be related to the biological effectiveness of antibodies. The aim of the present study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Saalman et al [29] also observed that the avidity of IgG-AGA was preserved during remission on a gluten-free diet, despite a marked decrease in serum antibody concentration. Upon gluten challenge, most children showed a further increase in antibody avidity together with an elevated IgG-AGA level.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Saalman et al [29] also observed that the avidity of IgG-AGA was preserved during remission on a gluten-free diet, despite a marked decrease in serum antibody concentration. Upon gluten challenge, most children showed a further increase in antibody avidity together with an elevated IgG-AGA level.…”
Section: Discussionmentioning
confidence: 95%
“…In type 1 diabetes, affinity maturation seems to be dependent on the antigen specificity of the autoantibodies [28]. Also in CD, there is evidence of avidity maturation of diseaseassociated antibodies, as Saalman et al [29] showed that IgG antibodies to gliadin (IgG-AGA) and b-lactoglobulin in children with untreated CD were of higher avidity than corresponding antibodies from healthy children. In addition, Vainio et al [30] have reported significantly increased amounts of high-avidity IgA gliadin antibodies (IgA-AGA) during prolonged experience of the CD-associated condition dermatitis herpetiformis.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The elution method with the chaotropic agent sodium thiocyanate (NaSCN) has been described in previous publications [12][13][14]. For determination of antibody avidity, the serum dilution giving 50% of the maximum signal was determined by means of serial dilutions, as described above, and was used in a subsequent ELISA to determine avidity.…”
Section: Avidity Assaysmentioning
confidence: 99%